Mnemonic and behavioral effects of biperiden, an M1-selective antagonist, in the rat - Popelíková, Anna; Bahník, Štěpán; Lobellová, Veronika; Svoboda, Jan; Stuchlík, Aleš (Psychopharmacology, 2018)
RATIONALE: There is a persistent pressing need for valid animal models of cognitive and mnemonic disruptions (such as seen in Alzheimer's disease and other dementias) usable for preclinical research. OBJECTIVES: We have set out to test the validity of administration of biperiden, an M1-acetylcholine receptor antagonist with central selectivity, as a potential tool for generating a fast screening model of cognitive impairment, in outbred Wistar rats. METHODS: We used several variants of the Morris water maze task: (1) reversal learning, to assess cognitive flexibility, with probe trials testing memory retention; (2) delayed matching to position (DMP), to evaluate working memory; and (3) "counter-balanced acquisition," to test for possible anomalies in acquisition learning. We also included a visible platform paradigm to reveal possible sensorimotor and motivational deficits. RESULTS: A significant effect of biperiden on memory acquisition and retention was found in the counter-balanced acquisition and probe trials of the counter-balanced acquisition and reversal tasks. Strikingly, a less pronounced deficit was observed in the DMP. No effects were revealed in the reversal learning task. CONCLUSIONS: Based on our results, we do not recommend biperiden as a reliable tool for modeling cognitive impairment.
Keywords: Reversal Learning; Behavior, Animal; modely nemocí na zvířatech; Male; Rats, Wistar; poruchy paměti; krátkodobá paměť; Maze Learning; kognitivní dysfunkce; antagonisté muskarinových receptorů; Biperiden; Alzheimerova nemoc; Alzheimer Disease; biperiden; mužské pohlaví; potkani Wistar; Cognitive Dysfunction; krysa rodu Rattus; bludiště - učení; Animals; zvířata; Rats; Disease Models, Animal; chování zvířat; reverzní učení; Memory Disorders; Memory, Short-Term; Muscarinic Antagonists